2020
DOI: 10.1186/s12885-020-07087-7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative adjuvant treatment strategy for hepatocellular carcinoma with microvascular invasion: a non-randomized interventional clinical study

Abstract: Background: Microvascular invasion (MVI) is considered to be one of the important prognostic factors that affect postoperative recurrence in patients with hepatocellular carcinoma (HCC) with variable results across their treatment options. This study was carried out to investigate efficacy of postoperative adjuvant RT in HCC patients with MVI. Methods: This was single center, prospective study carried out in HCC patients with MVI, aged 35-72 years. All patients were non-randomly allocated to receive standard p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…The presence of MVI is considered as an independent prognostic factor associated with the early recurrence and poor survival after both resection and transplantation (Lim et may be suitable for the patient with small-size HCC displayed MVI (Imai et al 2018; Lee et al 2021) because it has been reported that among the patients with high risk of MVI, the cumulative 2-year recurrence rate was 90.0% in the surgical resection group, while 30.6% in the RFA group (Lee et al 2021). Furthermore, additional adjuvant or targeted therapies were reported to improve survival for HCC patients with MVI compared to surgical resection alone (Sun et al 2016; Wang et al 2020b;Zhang et al 2019). So preoperative prediction of MVI status is clinically signi cant for surgical decision making and other treatment strategies to improve patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of MVI is considered as an independent prognostic factor associated with the early recurrence and poor survival after both resection and transplantation (Lim et may be suitable for the patient with small-size HCC displayed MVI (Imai et al 2018; Lee et al 2021) because it has been reported that among the patients with high risk of MVI, the cumulative 2-year recurrence rate was 90.0% in the surgical resection group, while 30.6% in the RFA group (Lee et al 2021). Furthermore, additional adjuvant or targeted therapies were reported to improve survival for HCC patients with MVI compared to surgical resection alone (Sun et al 2016; Wang et al 2020b;Zhang et al 2019). So preoperative prediction of MVI status is clinically signi cant for surgical decision making and other treatment strategies to improve patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…HCC is still considered one of the most dreadful diseases that can cause an increased incidence of intrahepatic and extrahepatic metastasis with a high mortality rate in both developed and developing countries [ 1 , 56 ]. Due to its poor prognosis and lack of management with adjuvant therapies, the only treatment for HCC is hepatic resection and liver transplantation with the minimum outcome, systemic toxicity, distant metastasis, and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative adjuvant treatment, such as postoperative interventional therapy and radiotherapy, could improve the prognosis of HCC patients with MVI [ 31 , 32 ]. In our study, the postoperative interventional therapy/radiotherapy was not significantly associated with the prognosis of patients, which might be attributed to the different baseline data between patients with and without treatment and the small sample size.…”
Section: Discussionmentioning
confidence: 99%